POLITICAL RULE OF THE CUSHAN DYNASTY CAPTURE - Nuriddin Fatxullayev (Web of Journals Publishing, 2024)
In this article, we will discuss with you a great state-cushan Empire, which was one of the strongest countries in the world in its day and united the property of present-day Southern Uzbekistan, Southern Tajikistan, Afghanistan, Pakistan, and India.
Keywords: Yuechjis, Cushan Empire, Kudzula Kadfiz, Vima Kadfiz, Kanishka, geographical names of regions, coins, cultural, religious and religious names, political and economic life.